2001
DOI: 10.1088/0029-5515/41/11/310
|View full text |Cite
|
Sign up to set email alerts
|

Steady improved confinement in FTU high field plasmas sustained by deep pellet injection

Abstract: High density plasmas (n0 ≈ 8 × 10 20 m −3) featuring steady improved core confinement have been obtained in FTU up to the maximum nominal toroidal field (8 T) by deep multiple pellet injection. These plasmas also feature high purity efficient electron-ion coupling and peaked density profiles sustained for several confinement times. Neutron yields in excess of 1 × 10 13 n/s are measured, consistent with the reduction of the ion transport to neoclassical levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Figure 1 highlights that in LLL-FTU plasmas the core electron density increases together with the amount of injected gas, resulting in the peaking of the electron density profile. The density peaking factor 5 achieved in these discharges is around 2 which is similar to those obtained in FTU pellet injection experiments [15,16]. In [16] it was shown that pellet injected discharges reaching densities above the threshold for the saturated ohmic confinement (SOC) scaling were recovering the Neo-Alcator scaling with density.…”
Section: Lll-ftu Reference Dischargesupporting
confidence: 80%
“…Figure 1 highlights that in LLL-FTU plasmas the core electron density increases together with the amount of injected gas, resulting in the peaking of the electron density profile. The density peaking factor 5 achieved in these discharges is around 2 which is similar to those obtained in FTU pellet injection experiments [15,16]. In [16] it was shown that pellet injected discharges reaching densities above the threshold for the saturated ohmic confinement (SOC) scaling were recovering the Neo-Alcator scaling with density.…”
Section: Lll-ftu Reference Dischargesupporting
confidence: 80%
“…The injection of solid pellets of frozen fuel in a wide velocity range (50-3000 m s −1 ) has proven to be an efficient method for raising the density of tokamak plasmas. The peaked density profiles thus obtained are often associated with improved core energy confinement, which has been observed on several machines [1][2][3][4][5][6]. In general, the particle deposition due to the pellet injection has a combined effect both on the electron density and on the plasma current density profile.…”
Section: Introductionmentioning
confidence: 91%
“…Two pellet injectors are currently available on FTU: a horizontal injector for low-field side fuelling, shooting 3 mm in diameter cylindrical deuterium pellets (10 21 particles) at a maximum speed of 1.3 km s −1 , and a vertical injector located at the same toroidal position injecting deuterium pellets of the same size from the high-field side and at a reduced speed of 500 m s −1 . Pellet penetration depends on the temperature of the target: in the experiments analysed here pellets have been injected on plasma targets with a central temperature in the range 1.5-2.0 keV and the ablation is found to occur at about one-third of the plasma minor radius [4,5] (r/a ∼ 0.3, which in these plasmas corresponds approximately to the position of the q = 1 resonant surface). Pellet-fuelled discharges, which exhibit enhanced confinement above the ITER97-L scaling, qualitatively recover the linear dependence of τ E on the lineaveraged density (neo-Alcator type scaling τ E = kn e q 1.42 , and k = 7.1); this effect was also shown in [3] with the inclusion of post-pellet enhanced τ E in discharges at various currents.…”
Section: Confinement In Gas-fuelled and Pellet-fuelled Ohmic Dischargesmentioning
confidence: 99%